The Actualization of Maqamat and Ahwal in Modern Life (Study of the Naqsyabandiyah Babussalam Congregation, Langkat) - Sabaruddin Bisri; Sukiman; Muzakkir (Budapest International Research and Critics University, 2022)
The study deals with the actualization of maqamat and ahwal in modern life (study of the naqsyabandiyah Babussalam congregation, Langkat). The purpose of writing this article is to find out the following: 1) Understanding and practicing maqâmat and aḥwâl in the Naqsyabandiyah Babussalam congregation, Langkat; 2) Implementation of maqâmat and aḥwâl on the pilgrims of the Naqsyabandiyah Babussalam congregation, Langkat; and 3) Efforts to implement maqâmat and aḥwâl of the salik and congregations of the Naqsabandiyah Babussalam congregation, Langkat.. It can be concluded that the understanding of maqâmat and aḥwâl in the Naqsyabandiyah Babussalam Langkat congregation, the existence of a maqâmat linkage in the formation of akhlaq al-karîmah means that it can be understood that information on spiritual experience which is also known as inner view as a sign for the sālik when dhikr can also contribute to every sālik as a good Sufi as knowledge and as a driving force for changes in mental attitudes and noble character. So that it can help the sālik to undergo various maqāmat, in order to achieve a good state (aḥwāl). In addition, there is a strong interaction between the mursyid/master teacher and the saints through tawajjuh, recitation, and suluk